2016
DOI: 10.1016/j.compedu.2016.01.014
|View full text |Cite
|
Sign up to set email alerts
|

How do online course design features influence student performance?

Abstract: Given the rapid growth in online coursework within higher education, it is important to establish and validate quality standards for these courses. While many online learning quality rubrics do exist, thus far there has been little empirical evidence establishing a clear link between specific course design features and concrete, student-level course outcomes. In the current study, the authors develop an online course design assessment rubric that includes four areas, and explore the impact of each area on stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
253
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 362 publications
(273 citation statements)
references
References 36 publications
11
253
0
9
Order By: Relevance
“…Numerosos estudios han comparado los efectos de los programas online frente a los presenciales (i.e., Bernard et al, 2004;Jaggars y Xu, 2016). En el caso de las matemáticas, Russell, Kleiman, Carey y Douglas (2009) compararon los efectos de un programa de matemáticas realizado de forma presencial frente al mismo programa realizado vía online, sobre las creencias pedagógicas, las prácticas de instrucción y la comprensión de la enseñanza del sentido numérico y conceptos matemáticos relacionados, sin encontrar diferencias entre ambos, aunque los profesores que participaron en el curso online mostraron mayor interés por participar de nuevo en otros programas de formación.…”
unclassified
“…Numerosos estudios han comparado los efectos de los programas online frente a los presenciales (i.e., Bernard et al, 2004;Jaggars y Xu, 2016). En el caso de las matemáticas, Russell, Kleiman, Carey y Douglas (2009) compararon los efectos de un programa de matemáticas realizado de forma presencial frente al mismo programa realizado vía online, sobre las creencias pedagógicas, las prácticas de instrucción y la comprensión de la enseñanza del sentido numérico y conceptos matemáticos relacionados, sin encontrar diferencias entre ambos, aunque los profesores que participaron en el curso online mostraron mayor interés por participar de nuevo en otros programas de formación.…”
unclassified
“…This underperformance is even more prevalent in community college online education (Jaggars & Xu, 2016;Capra 2014Capra , 2011Moore & Kearsley, 2012). Although states, institutions, and foundations have invested resources to improve student success, their efforts have not substantially improved course completion rates (Tinto, 2011).…”
Section: Chapter Two: Literature Reviewmentioning
confidence: 99%
“…Although the statistical data about the overall enrollments in Massachusetts community colleges online education are sparse, this researcher found that online enrollment at these institutions has grown from 16,273 to approximately 20,261since the fall of 2012 (National Center for Education Statistics, 2014). Despite a continuous growth in online enrollment, student success and pass rates are declining (Jaggars & XU, 2016;Fishman 2015;Johnson & Mejia, 2014) at both local and national levels.…”
Section: Rationale and Significancementioning
confidence: 99%
See 2 more Smart Citations